2008
DOI: 10.1104/pp.107.112458
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Data-Mining Strategies for the Analysis of Direct-Infusion Ion Trap Mass Spectrometry Data from the Association of Perennial Ryegrass with Its Endophytic Fungus,Neotyphodium lolii     

Abstract: Direct-infusion mass spectrometry (MS) was applied to study the metabolic effects of the symbiosis between the endophytic fungus Neotyphodium lolii and its host perennial ryegrass (Lolium perenne) in three different tissues (immature leaf, blade, and sheath). Unbiased direct-infusion MS using a linear ion trap mass spectrometer allowed metabolic effects to be determined free of any preconceptions and in a high-throughput fashion. Not only the full MS 1 mass spectra (range 150-1,000 mass-to-charge ratio) were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 94 publications
0
65
0
Order By: Relevance
“…Although this type of analysis does not allow the establishment of direct and causal relationships between a certain metabolite and insect population responses, the differential pattern of these responses is intriguing and warrants further metabolomics studies on the effects of non-alkaloid metabolites on insect and other herbivores. A recent study also performed in our lab and using untargeted direct infusion ion trap mass spectrometry revealed the presence of formerly unknown compounds produced in endophyte infected plants (Cao et al 2008). Some of these compounds belong to the class of cyclic oligopeptides, which have been shown to be potentially antimicrobial (Arai et al 1973, Strobel andHess 1997;Seto et al 2007) and it is therefore possible that some of the plant protecting effects seen in endophyte infected plants are due to these or other, still completely unknown, endophyte specific compounds.…”
Section: Effects Of N Lolii Endophytes On Insect Herbivoresmentioning
confidence: 83%
“…Although this type of analysis does not allow the establishment of direct and causal relationships between a certain metabolite and insect population responses, the differential pattern of these responses is intriguing and warrants further metabolomics studies on the effects of non-alkaloid metabolites on insect and other herbivores. A recent study also performed in our lab and using untargeted direct infusion ion trap mass spectrometry revealed the presence of formerly unknown compounds produced in endophyte infected plants (Cao et al 2008). Some of these compounds belong to the class of cyclic oligopeptides, which have been shown to be potentially antimicrobial (Arai et al 1973, Strobel andHess 1997;Seto et al 2007) and it is therefore possible that some of the plant protecting effects seen in endophyte infected plants are due to these or other, still completely unknown, endophyte specific compounds.…”
Section: Effects Of N Lolii Endophytes On Insect Herbivoresmentioning
confidence: 83%
“…Since we know that a large range of metabolites varies with endophyte infection, strain and concentration, the overriding conclusion from these results is that alkaloids are certainly not the only factors, and may not even be the most important factor in the endophyte-grass-herbivore story. Furthermore, we also know that in addition to the known alkaloids, there are a range of other endophyte specific metabolites that have just recently been discovered and which may have biological activity as well, 21 but were not part of our analysis. A note of caution should be added here as well, as we have not included possible insect species interactions into our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that nutrients are taken up from the apoplast (Hinton & Bacon, 1985), or they might be transported to the fungus at the site of attachment to plant cells, but to date, no nutrient transporters have been identified or functionally characterized from fungal endophytes. Targeted (GC-MS, HPLC) and untargeted (direct infusion MS) metabolomics analyses of the L. perenne/ N. lolii association (Rasmussen et al, 2007(Rasmussen et al, , 2008aCao et al, 2008) demonstrated major shifts in primary metabolites in infected compared to endophyte free tissues. A strong reduction in free nitrate, the amino acids asparagine and proline, and proteins, and a concomitant increase in soluble carbohydrates (glucose, fructose, sucrose, fructans), organic acids (quinate, shikimate) and phenylpropanoids (chlorogenic acid) indicate an increase in C/N ratios and defence compounds (Rasmussen et al, 2008a).…”
Section: Neotyphodium -Grass Associationsmentioning
confidence: 99%
“…Even though alkaloids are usually perceived as the major factor affecting insect herbivores, a linear regression analysis of metabolic profiles with insect abundances indicated that a particular 'type' of metabolic composition, rather than any one individual compound, might be important for specific insect responses (Rasmussen et al, 2008b). Moreover, untargeted DIMS metabolic profiling also identified the presence of a previously unknown class of cyclic oligopeptides in endophyte infected samples, which might be relevant to ecological effects of these symbiotic associations as well (Cao et al, 2008).…”
Section: Neotyphodium -Grass Associationsmentioning
confidence: 99%